Kelimpahan dan Keanekaragaman Collembola dan Hubungannya dengan Tingkat Kesuburan Tanah Lahan Percontohan Reklamasi Tambang Timah Desa Bukit Layang, Bangka: Collembola Abundance and Diversity and Its Correlation With Soil Fertility Status of Tin Mine Pilot Reclamation Project Bukit Layang Village, Bangka - Frista Chairunnisa; Rion Apriyadi; Riko Irwanto (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2022)
Bangka Island is the largest tin producer in Indonesia, dominated by onshore mining. Various ex-tin mining land reclamation programs have been implemented in Bangka and to monitor its success, indicators that characterize soil quality improvement are needed. One of the bioindicators that has potential as an indicator of the success of the reclamation program is the soil mesofauna community, such as Collembola (Springtail). Further research and variations in the correlation of data are needed to support this statement. This study calculates the abundance, diversity, species richness, evenness, and dominance of Collembola family associated with several soil fertility parameters. The research location is a pilot reclamation land of the alluvial inland tin mine “Air Kundur 3”. Seven families of Collembola were found with the abundance of 6,642 inviduals. The category of this land reclamation is low soil fertility. The results showed that an increase in the diversity, richness and evenness index values ​​was followed by an increase in the parameters C-Organic, Cation Exchange Capacity, thickness and dry weight of litter. The increase in the relative abundance and dominance of Collembola was followed by a decrease in the index of diversity, richness and evenness of species. This study confirm the prediction that the diversity, richness, and evenness index of Collembola species can be used as an indicator of soil fertility in post-tin mining reclamation.